Penyelesaian Konflik Yang Sehat Di Dalam Gereja Berdasarkan Eksposisi Kisah Para Rasul - Siregar, Jonri Muksen (SAINT PAUL'S REVIEW, 2025)
Church conflicts have occurred since the early church to the present, so most of the conflicts have an impact on the formation of various church traditions or denominations. In general, factors that cause conflict within the church, among others; due to theological factors and non-theological factors. This study aims to test and explain about a leader and his qualifications, the church as one body in Jesus. the development of church conflicts in Indonesia and their resolution, so that mistakes are not repeated in the future and the implications for the church today. This research is qualitative which is a research procedure that produces descriptive data that is done with an approach to a person or something in oral or written form. In the process researchers use qualitative research methods of theology related to biblical studies. Biblical theological research includes exposition theology and Biblical studies. Conclusion; To resolve healthy conflicts within the church in Acts, leaders take an important role. The criteria of the servants are well-behaved, "filled with Spirit and Wisdom" and "Laying on Hands". Shepherds are the highest decision makers. Every decision that has been decided by the leader, must be followed and implemented by all congregations. Biblical leadership becomes very important, because the leader or pastor of the congregation becomes the center of the teaching and development of the church. If there is a deviation the Leader must firmly discipline in biblical ways. The only biblical reason for separation is when the main truth of the Gospel is denied (Galatians 1:6-10; 1 John 2:18-19).